The Little green data book 2003 (World Bank, 2003)
"The Little Green Data Book 2003 is a pocket-sized ready reference on key environmental data for over 200 countries. Key indicators are organized under the headings of agriculture, forestry, biodiversity, energy, emission and pollution, and water and sanitation. The World Bank's mission is to fight poverty for lasting results. Enhancing environmental quality, improving natural resource management, and maintaining global ecosystems are all important steps towards this goal, and The Little Green Data Book provides a baseline against which to measure progress."